Role of sarcopenia in the frailty transitions in older adults: a population‐based cohort study. Issue 5 (28th July 2022) - Álvarez‐Bustos, Alejandro; Carnicero‐Carreño, Jose Antonio; Davies, Betty; Garcia‐Garcia, Francisco Javier; Rodríguez‐Artalejo, Fernando; Rodríguez‐Mañas, Leocadio; Alonso‐Bouzón, Cristina
Abstract: Background: Frailty and sarcopenia are age‐associated syndromes that have been associated with the risk of several adverse events, mainly functional decline and death, that usually coexist. However, the potential role of one of them (sarcopenia) in modulating some of those adverse events associated to the other one (frailty) has not been explored. The aim of this work is to assess the role of sarcopenia within the frailty transitions and mortality in older people. Methods: Data from the Toledo Study of Healthy Aging (TSHA) were used. TSHA is a cohort of community‐dwelling older adults ≥65. Frailty was assessed according with the Frailty Phenotype (FP) and the Frailty Trait Scale‐5 (FTS5) at baseline and at follow‐up. Basal sarcopenia status was measured with the standardized Foundation for the National Institutes of Health criteria. Fisher's exact test and logistic regression model were used to determine if sarcopenia modified the transition of frailty states (median follow‐up of 2.99 years) and Cox proportional hazard model was used for assessing mortality. Results: There were 1538 participants (74.73 ± 5.73; 45.51% men) included. Transitions from robustness to prefrailty and frailty according to FP were more frequent in sarcopenic than in non‐sarcopenic participants (32.37% vs. 15.18%, P  ≤ 0.001; 5.76% vs. 1.12%; P  ≤ 0.001, respectively) and from prefrailty‐to‐frailty (12.68% vs. 4.27%; P  = 0.0026). Improvement from prefrail‐to‐robust and remaining robust was more frequent in non‐sarcopenic participants (52.56% vs. 33.80%, P  ≤ 0.001; 80.18% vs 61.15%, P  ≤ 0.001, respectively). When classified by FTS5, this was also the case for the transition from non‐frail‐to‐frail (25.91% vs. 4.47%, P  ≤ 0.001) and for remaining stable as non‐frail (91.25% vs. 70.98%, P  ≤ 0.001). Sarcopenia was associated with an increased risk of progression from robustness‐to‐prefrailty [odds ratio (OR) 2.34 (95% confidence interval, CI) (1.51, 3.63); P  ≤ 0.001], from prefrailty‐to‐frailty [OR(95% CI) 2.50 (1.08, 5.79); P  = 0.033] (FP), and from non‐frail‐to‐frail [OR(95% CI) 4.73 (2.94, 7.62); P ‐value ≤ 0.001]. Sarcopenia does not seem to modify the risk of death associated with a poor frailty status (hazard ratios (HR, 95%) P  > 0.05). Conclusions: Transitions within frailty status, but not the risk of death associated to frailty, are modulated by the presence of sarcopenia.